A Numerical Simulation for Heat Conduction in Anisotropic FGMs of Space-time Dependent Conductivities with Arbitrary Initial Conditions and Source Terms - Azis, Mohammad Ivan; Firman, Firman; Muh. Nur, Muh. Nur; M. Yusup, Eliza (semarak ilmu, 2025)
Numerical solutions of unsteady heat conduction problems with arbitrary initial conditions and source terms for anisotropic functionally graded materials (FGMs) of spatiotemporal dependent conductivity are sought. The variable reduction transformation and Laplace transform (LT) were combined to derive a domainboundary integral equation. Numerical solutions were obtained using a standard domain-boundary element method (DBEM) and the Stehfest formula. The accuracy of the numerical method is also evaluated. It can be concluded that the LT-DBEM is efficient and accurate.